1982
DOI: 10.1111/j.1365-2125.1982.tb04957.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamines and visual function: studies on dynamic acuity and the pupillary response to light.

Abstract: 1 Effects of three antihistamines, triprolidine (10 mg) in a sustained release form, astemizole (10 mg) and terfenadine (60 mg), have been studied on dynamic visual acuity and on the response of the pupil to light, together with critical flicker fusion, digit symbol substitution and cancellation, and subjective assessment of mood. The study was double‐blind and effects were observed from 0.5‐4.0 h after ingestion. 2 Triprolidine impaired dynamic acuity and reduced the threshold for subjective fusion of a flick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…In comparison to pheniramine maleate the side effects were also much less with Cetirizine and Astemizole (Table IV). However, in our study incidence of side effects were much higher in comparision of previous reported studies in whom Cetirizine and Astemizole were claimed to be devoid of CNS side effects and anti cholinergic effects (Callier et al, 1981), wilson and Hillas (1982), Nicolson et al, 1982 andVijay et al, 1994). The higher incidence of these side effects in our study might be because of the fact that we specifically asked regarding these effects from all such patients who failed to volunteer any adverse effects of the drug.…”
Section: Discussionsupporting
confidence: 74%
“…In comparison to pheniramine maleate the side effects were also much less with Cetirizine and Astemizole (Table IV). However, in our study incidence of side effects were much higher in comparision of previous reported studies in whom Cetirizine and Astemizole were claimed to be devoid of CNS side effects and anti cholinergic effects (Callier et al, 1981), wilson and Hillas (1982), Nicolson et al, 1982 andVijay et al, 1994). The higher incidence of these side effects in our study might be because of the fact that we specifically asked regarding these effects from all such patients who failed to volunteer any adverse effects of the drug.…”
Section: Discussionsupporting
confidence: 74%
“…HR1 antagonists decrease the critical flicker fusion frequency. [59][60][61][62] The responses of macaque parasol ganglion cells to luminance flicker are identical to those of human subjects under the same conditions, 63 and it is possible that the antihistamines act on the neural circuit providing input to parasol cells. In rats, dopaminergic neurons express HR1 (Fig.…”
Section: Retinopetal Axons Containing Histaminementioning
confidence: 71%
“…Mann, Crowe, & Tietze (1989) and Woodward (1990) have described the chemistry, pharmacology, pharmacokinetics, clinical efficacy, adverse effects, and dosages of many of the nonsedating histamine HIreceptor antagonists and their differences with traditional antihistamines such as diphenhydramine (Benadryl) and chlorpheniramine. Terfenadine has shown little or no performance impairment when compared to the significant performance impairments shown with centrally acting antihistamines such as diphenhydramine (Betts, Markman, L••benham, Mortiboy & McKevitt, 1984;Clarke & Nicholson, 1978;Cohen, Hamilton, & Peck, 1987;Fink & Irwin, 1979;Gaillard, Gruisen, & de Jong, 1988;Goetz, Jocobsen, Murnarne, Reid, Repperger, Goodyear, & Martin, 1989;Kulshrestha, Gupta, Turner, & Wadsworth, 1978;Moskowitz & Burns, 1988;Nicholson, Smith, & Spencer, 1982;Nicholson & Stone, 1986;and Schilling, Adamus, & Kuthan, 1990). Performance was assessed in asymptomatic adults with simple tasks such as reaction time, adaptive tracking, continuous memory, visual search, visuo-motor coordination, dynamic visual acuity, digit symbol substitution, divided attention, vigilance, finger tapping, body sway, eye movements, critical flicker fusion and wfth subjective scales such as mental status surveys, self-rating scales to assess mood state, and symptom questionnaires.…”
Section: Medicationsmentioning
confidence: 99%